Protest Movements in Asylum and Deportation - Rosenberger, Sieglinde; Stern, Verena; Merhaut, Nina (IMISCOE Research Series, 2018)
Protest mobilization and outcome; Political participation; Emotions and social ties; Deportation nation; Refugees; Pro-migrant protest; Anti-migrant protest